2013
DOI: 10.7498/aps.62.110201
|View full text |Cite
|
Sign up to set email alerts
|

A type of the new exact and approximate conserved quantity deduced from Mei symmetry for a weakly nonholonomic system

Abstract: A type of structural equation, new exact and approximate conserved quantity which are deduced from Mei symmetry of Lagrange equations for a weakly nonholonomic system, are investigated. First, Lagrange equations of weakly nonholonomic system are established. Next, under the infinitesimal transformations of Lie groups, the definition and the criterion of Mei symmetry for Lagrange equations in weakly nonholonomic systems and its first-degree approximate holonomic system are given. And then, the expressions of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The non-holonomic system can be used directly to obtain the holonomic system for the differential equation corresponding to motion. Under the Lie group of infinitesimal transformation, for the weak non-holonomic system, Han et al suggested the new Mei symmetries of the exact and approximate nature of the Lagrange equation [9]. The inverse problem of the Mei symmetries of non-holonomic systems with variable mass was proposed by Huang and Cai [10].…”
Section: Introductionmentioning
confidence: 99%
“…The non-holonomic system can be used directly to obtain the holonomic system for the differential equation corresponding to motion. Under the Lie group of infinitesimal transformation, for the weak non-holonomic system, Han et al suggested the new Mei symmetries of the exact and approximate nature of the Lagrange equation [9]. The inverse problem of the Mei symmetries of non-holonomic systems with variable mass was proposed by Huang and Cai [10].…”
Section: Introductionmentioning
confidence: 99%
“…The non-holonomic system can be used directly to obtain the holonomic system for the differential equation corresponding to motion. Under the Lie group of infinitesimal transformation, for the weak non-holonomic system, Han et al suggested the new Mei symmetries of the exact and approximate nature of the Lagrange equation [11]. The inverse problem of the Mei symmetries of nonholonomic systems with variable mass was proposed by Huang and Cai [12].…”
Section: Introductionmentioning
confidence: 99%